Structural and EPR Studies of Pyrophosphate-Bridged Dinuclear CuII Complexes - Sartoris, Rosana Patricia (2014)
Two new pyrophosphate-bridged copperII complexes, [Cu(dpa)(H2O7P2)]21 and [Cu2(terpy)2(HO7P2)·(H2O4P)·(H3O4P)·(H2O)] 2 (dpa = 2,2′-dipyridylamine and terpy = 2,2′:6′,2″-terpyridine) were isolated and their crystal structures determined by single-crystal X-ray diffraction. The compounds are triclinic and contain dinuclear copperII units bridged by pyrophosphate anions. The EPR spectra observed in three planes of single crystal samples as a function of field orientation at 293 K for compounds 1 and 2, and also for two other pyrophosphate compounds already reported, [Cu(bipy)(cis-H2O7P2)]2·3(H2O) 3 and [Cu(bipy)(trans-H2P2O7)]24 display a single resonance for any field orientation and temperatures T between 4 and 293 K, as in mononuclear spin systems, without hyperfine structure, and their g-factors and line widths were measured. The relations between the principal directions of the g-matrices and the molecular structures are discussed and compared with related compounds. The temperature dependences of the intensity of the EPR signals observed for 1–4 above 4 K indicate a paramagnetic Curie behavior, with no indication of intradinuclear exchange interactions (so, |J| < 2 K). The absence of dinuclear splitting and of hyperfine structure of the dinuclear units is explained in terms of averaging out by the interdinuclear interactions, allowing to set a lower limit of their magnitudes.